First record of the Aztec Rail (Rallus tenuirostris) in Coahuila, Mexico - Julie Ibarra-Rossow; Jorge Luis Cortinas-Salazar; Omar Suárez-García (Huitzil)
Historically, the Aztec Rail (Rallus tenuirostris) has been recorded in the wetlands of the Mexican Transvolcanic Belt, and recently in wetlands and along river edges in Chihuahua and Durango. As participants in a citizen science birdwatching collective that regularly visits the small artificial wetland of La Partida, Torreón, we obtained the first record of the species in Coahuila, northern Mexico. On 16 January 2024, we spotted a rail-like bird among the vegetation. We photographed the individual, which we later identified as an Aztec Rail by the grayish head, cinnamon malar coloration, white chin and throat, rufous chest and belly, dark central dorsal feathers surrounded by light gray, and white undertail coverts. Our observation represents a distributional range extension for the species, highlights the ecological importance of the small wetlands of northern Mexico that are habitats for waterbirds, and exemplifies the value of citizen science programs to better understand species distributions.